2020
DOI: 10.3389/fpsyg.2020.00573
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Mental Health and the Education Level in Elderly People: Mediation of Leisure Attitude

Abstract: Purpose: The present study intends to explore the influence of education on the mental health of retired people and the mediating role of a leisure attitude in this relationship.Design/Methodology: The sample was simple random, and a confidentiality agreement was established. The sample was composed of 403 Portuguese participants (37.2% male; 62.8% female). The participants completed the MHI and the LAS.Findings: The hypothesized mediation model showed that a leisure attitude mediated the association between e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 64 publications
7
31
0
Order By: Relevance
“…Pompili et al [38] explained that individuals with higher educational achievement may be more prone to suicide risk when facing failures, public shame, and high premorbid functioning. However, several previous studies found the opposite results [32,[39][40][41]. Belo et al [39] reported that old-age people with high education have a better psychological adjustment concerning well-being, which is in consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Pompili et al [38] explained that individuals with higher educational achievement may be more prone to suicide risk when facing failures, public shame, and high premorbid functioning. However, several previous studies found the opposite results [32,[39][40][41]. Belo et al [39] reported that old-age people with high education have a better psychological adjustment concerning well-being, which is in consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…However, several previous studies found the opposite results [32,[39][40][41]. Belo et al [39] reported that old-age people with high education have a better psychological adjustment concerning well-being, which is in consistent with our results. Oh et al's study [40] in Korea found that elderly people with low education level were associated with the risk of incident suicidality.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that high education levels and positive leisure attitudes are important parameters in terms of psychological well‐being in the elderly population. 25 Another study from a sample of elderly subjects in the north of Portugal showed that elderly individuals with lower level of education tended to have higher values for both depression and anxiety. 26 …”
Section: Discussionmentioning
confidence: 99%
“…In the health field, involvement in leisure activities promotes physical health, positive social interactions, psychological well-being and quality of life 5,7,9 . Thus, leisure can be considered as a conditioner and determinant of the health-disease process, especially regarding mental health 10 . In addition, involvement in leisure activities is a predictor of health self-perception and functional capacity in the older adults, and some leisure activities are related to healthpromoting behavior 11 .…”
Section: Introductionmentioning
confidence: 99%
“…People's practices during leisure says more about their attitude than in any other context 4,10,12 . Therefore, it is relevant to know the attitude of the older people in relation to leisure in order to allow a better understanding of this type of social practice and stimulate more positive attitudes and engagement in leisure activities 6,13 .…”
Section: Introductionmentioning
confidence: 99%